Expression, purification and crystallization of N‐acetyl‐(R)‐β‐phenylalanine acylases derived from Burkholderia sp. AJ110349 and Variovorax sp. AJ110348 and structure determination of the Burkholderia enzyme. Issue 3 (23rd February 2023) - Kato, Yuki; Kawasaki, Hisashi; Nakamatsu, Tsuyoshi; Matsuda, Namio; Natsume, Ryo
Abstract : The structure of N ‐acetyl‐( R )‐β‐phenylalanine acylase from Burkholderia sp. AJ110349 was determined. The three domains showed structural similarity to the corresponding domains of the large subunit of N, N ‐dimethylformamidase from Paracoccus sp. strain DMF, despite the quaternary structures of these holoenzymes in solution being completely different from each other. Abstract : N ‐Acetyl‐( R )‐β‐phenylalanine acylase is an enzyme that hydrolyzes the amide bond of N ‐acetyl‐( R )‐β‐phenylalanine to produce enantiopure ( R )‐β‐phenylalanine. In previous studies, Burkholderia sp. AJ110349 and Variovorax sp. AJ110348 were isolated as ( R )‐enantiomer‐specific N ‐acetyl‐( R )‐β‐phenylalanine acylase‐producing organisms and the properties of the native enzyme from Burkholderia sp. AJ110349 were characterized. In this study, structural analyses were carried out in order to investigate the structure–function relationships of the enzymes derived from both organisms. The recombinant N ‐acetyl‐( R )‐β‐phenylalanine acylases were crystallized by the hanging‐drop vapor‐diffusion method under multiple crystallization solution conditions. The crystals of the Burkholderia enzyme belonged to space group P 41 21 2, with unit‐cell parameters a = b = 112.70–112.97, c = 341.50–343.32 Å, and were likely to contain two subunits in the asymmetric unit. The crystal structure was solved by the Se‐SAD method, suggesting that two subunits in the asymmetric unit form a dimer. Each subunit was composed of three domains, and they showed structural similarity to the corresponding domains of the large subunit of N, N ‐dimethylformamidase from Paracoccus sp. strain DMF. The crystals of the Variovorax enzyme grew as twinned crystals and were not suitable for structure determination. Using size‐exclusion chromatography with online static light‐scattering analysis, the N ‐acetyl‐( R )‐β‐phenylalanine acylases were clarified to be dimeric in solution.